Electrode and preparation method thereof, electrochemical device and electronic device
By performing thermogravimetric analysis of the electrode active material layer under an inert atmosphere, the problem of the electrochemical device decreasing conductivity when increasing the electrode thickness is solved, and the energy density of the electrochemical device is improved.
Patent Information
- Application Number
- CN202180026343.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-15
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2041-11-15
AI Technical Summary
In the process of increasing the electrode thickness to increase the energy density, existing electrochemical devices can easily lead to a decrease in the conductivity of the active material layer, affecting the performance of the electrochemical device.
The active material layer of the electrode was subjected to thermogravimetric analysis at a temperature increase of 10°C/min under an inert atmosphere to ensure that the mass change of the active material layer from 200°C to 350°C is 0% to 0.2%, thereby improving the conductivity.
By improving the conductivity of the active material layer, the thickness of the electrode can be increased without deteriorating the performance of the electrochemical device, thereby increasing the energy density of the electrochemical device.
Smart Images

Figure CN115398668B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical energy storage, and in particular to electrodes and preparation methods thereof, electrochemical devices and electronic devices. Background Art
[0002] Electrochemical devices, such as lithium-ion batteries, have the advantages of high energy density, high power, and long cycle life, and are widely used in various fields. With the development of technology, the requirements for the energy density of electrochemical devices are getting higher and higher. In order to improve the energy density of electrochemical devices, some technologies increase the capacity or voltage of active materials, and other technologies increase the content of active materials per unit volume and reduce the content of inactive materials. The proportion of inactive substances can be reduced by reducing the thickness of the current collector or the separator, reducing the proportion of inactive materials in the formula, and preparing thicker electrodes. However, in actual application, the thickness of the current collector and the separator has been reduced to near the limit, so the electrode thickness can only be increased. However, excessive increase in the thickness of the electrode may affect the performance of the electrochemical device, so the thickness of the electrode cannot be significantly increased. Therefore, how to increase the thickness of the electrode as much as possible to increase the capacity of the electrochemical device while ensuring the performance of the electrochemical device is an urgent problem to be solved. Summary of the invention
[0003] Some embodiments of the present application provide an electrode and a method for preparing the same, an electrochemical device and an electronic device, wherein the active material layer of the electrode is subjected to thermogravimetric analysis at a heating rate of 10°C / min under an inert atmosphere, and the results of the thermogravimetric analysis show that the mass change of the active material layer at 200°C to 350°C is 0% to 0.2%, thereby improving the conductivity of the active material layer, which in turn helps to increase the thickness of the active material layer to improve the energy density of the electrochemical device.
[0004] In some embodiments of the present application, an electrode is proposed, including: a current collector and an active material layer disposed on at least one surface of the current collector; the active material layer is subjected to thermogravimetric analysis at a heating rate of 10°C / min in an inert atmosphere, and the results of the thermogravimetric analysis show that the mass change of the active material layer from 200°C to 350°C is 0% to 0.2%, which indicates that the content of polymer compounds with a decomposition temperature below 350°C in the active material layer in the present application is zero or extremely low, which is beneficial to improving the ion and electron conduction in the active material layer. In some embodiments, the polymer compound with a decomposition temperature below 350°C comes from the binder and / or thickener in the electrode. In some embodiments, the active material layer contains almost no polymer compounds with a low decomposition temperature, which is beneficial to improving the conductivity and thus improving the energy density.
[0005] In some embodiments of the present application, the results of thermogravimetric analysis show that the number of weight loss peaks of the active material layer at 200°C to 350°C is 0, and the number of weight loss peaks of the active material layer at 350°C to 800°C is not less than 1. This shows that the active material layer in the present application has good conductivity, which is beneficial to increase the thickness of the electrode, and further to increase the capacity and energy density of the electrochemical device.
[0006] In some embodiments, the results of thermogravimetric analysis show that the mass change of the active material layer at 350°C to 800°C is 0.21% to 13%. In some embodiments, the results of thermogravimetric analysis show that the mass change of the active material layer at 350°C to 800°C is 0.77% to 3.4%.
[0007] In some embodiments of the present application, the electrode is a negative electrode. In some embodiments, the electrode is a negative electrode, and the compaction density of the active material layer is ρ ≥ 0.6 g / cm 3 , a higher compaction density is beneficial to increase the energy that can be stored per unit volume of the electrochemical device. In some embodiments, the thickness of the active material layer on one side of the current collector h ≥ 10μm, and the thicker thickness is beneficial to carrying more active materials, thereby improving the energy density of the electrochemical device. In some embodiments, the bonding force F between the active material layer and the current collector satisfies: 300N / m ≥ F ≥ 0.5N / m, which can ensure that there is sufficient bonding force between the active material layer and the current collector, and can prevent the problem of decreased conductivity caused by excessive bonding force and excessive binder. In some embodiments, the resistivity of the active material layer is 0.01Ω*cm to 50Ω*cm, which indicates that the active material layer of the present application has good conductivity, which is beneficial to the charge and discharge performance of the electrochemical device. In some embodiments, the active material layer includes a negative electrode material, and the negative electrode material includes at least one of lithium titanate, silicon oxide, graphite, silicon or hard carbon.
[0008] In some embodiments of the present application, the compaction density ρ of the active material layer satisfies: 1.85 g / cm 3 ≥ρ≥0.65g / cm 3 , which is conducive to improving the energy density of the electrochemical device. In some embodiments, the thickness h of the active material layer on one side of the current collector satisfies: 1500μm ≥ h ≥ 15μm, which is conducive to preventing the active material layer from falling off while improving the energy density of the electrochemical device. In some embodiments, the bonding force F between the active material layer and the current collector satisfies: 150N / m ≥ F ≥ 1N / m, thereby ensuring conductivity while improving the bonding force.
[0009] In some embodiments of the present application, the compaction density ρ of the active material layer satisfies: 1.83 g / cm 3 ≥ρ≥1.0g / cm 3In some embodiments of the present application, the thickness h of the active material layer on one side of the current collector satisfies: 150 μm ≥ h ≥ 30 μm. In some implementations of the present application, the bonding force F between the active material layer and the current collector satisfies: 20 N / m ≥ F ≥ 1 N / m.
[0010] In some embodiments of the present application, the active material layer includes a conductive agent, and the conductive agent includes at least one of carbon nanotubes, carbon fibers, acetylene black, graphene, Ketjen black, or conductive carbon black. In some embodiments, the active material layer includes a conductive agent, and the mass percentage of the conductive agent in the active material layer is 0% to 2% based on the total mass of the active material layer.
[0011] In some embodiments, the active material layer includes a polymer compound, and the polymer compound includes at least one of polyethylene oxide, polypropylene oxide, polyvinylidene fluoride, polytetrafluoroethylene, polyacrylonitrile, polyimide, polysiloxane, polyacrylic acid, polypropylene derivatives, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polymethyl pyrrolidone, polyvinyl pyrrolidone, styrene acrylate or styrene-butadiene rubber. In some embodiments, the active material layer includes a polymer compound, and the mass percentage of the polymer compound in the active material layer is 0.22% to 14% based on the total mass of the active material layer. In some embodiments of the present application, the active material layer includes a polymer compound, and the mass percentage of the polymer compound in the active material layer is 0.8% to 3.5% based on the total mass of the active material layer.
[0012] In some embodiments of the present application, a method for preparing an electrode is proposed, which can be used to manufacture any electrode in the present application, comprising: applying a slurry of an active material layer to at least one surface of a current collector, drying, and cold pressing to obtain an initial electrode; treating the initial electrode to obtain an electrode; wherein treating the initial electrode comprises: plasma treating the initial electrode in a vacuum environment, the plasma power is 0.5kW to 5kW, the gas source comprises at least one of nitrogen, argon or carbon tetrafluoride, the gas flow rate is 3000sccm to 5000sccm, the temperature is 20°C to 60°C, and the treatment time is 1min to 60min; or, heat treating the initial electrode in a vacuum or inert gas environment, the heat treatment temperature is 200°C to 400°C, and the heat treatment time is not less than 5min; or, laser bombarding the initial electrode in a vacuum or inert gas environment, the laser intensity is 25W to 30W, and the treatment time is 1s to 600s.
[0013] In some embodiments of the present application, the initial electrode is subjected to plasma treatment in a vacuum environment, the plasma power is 1kW to 3kW, and the treatment time is 15min to 30min. In some embodiments of the present application, the initial electrode is subjected to plasma treatment in a vacuum environment, the plasma power is 3kW to 5kW, and the treatment time is 1min to 15min. In some embodiments of the present application, the initial electrode is subjected to heat treatment in a vacuum or inert gas environment, the heat treatment temperature is 200℃ to 250℃, and the heat treatment time is 180min to 300min. In some embodiments of the present application, the initial electrode is subjected to heat treatment in a vacuum or inert gas environment, the heat treatment temperature is 250℃ to 350℃, and the heat treatment time is 5min to 180min.
[0014] The present application also proposes an electrochemical device, comprising an electrode; the electrode is any electrode of the present application, or the electrode is an electrode prepared by the preparation method of the present application. The present application proposes an electronic device, comprising the electrochemical device proposed in the present application.
[0015] An electrode proposed in an embodiment of the present application includes a current collector and an active material layer arranged on at least one surface of the current collector; the active material layer is subjected to thermogravimetric analysis at a heating rate of 10°C / min under an inert atmosphere, and the results of the thermogravimetric analysis show that the mass change of the active material layer at 200°C to 350°C is 0% to 0.2%, which indicates that in the electrode proposed in the embodiment of the present application, the active material layer has good conductivity, which is beneficial to increase the thickness of the active material layer without deteriorating the performance, thereby facilitating improving the energy density of the electrochemical device. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The above and other features, advantages and aspects of the embodiments of the present disclosure will become more apparent with reference to the following detailed description in conjunction with the accompanying drawings. Throughout the accompanying drawings, the same or similar reference numerals represent the same or similar elements. It should be understood that the drawings are schematic and that components and elements are not necessarily drawn to scale.
[0017] Figure 1 is a schematic diagram of an electrode according to an embodiment of the present disclosure. DETAILED DESCRIPTION
[0018] The following embodiments may enable those skilled in the art to more fully understand the present application, but do not limit the present application in any way.
[0019] In order to improve the energy density of electrochemical devices, some technologies increase the energy density of electrochemical devices by increasing the thickness of the active material layer in the electrode. However, increasing the thickness of the active material layer in the electrode may deteriorate the conductivity of the active material layer due to the excessive thickness of the active material layer. In order to improve the conductivity of the active material layer, some technologies use a multi-layer active material layer structure, but the composite cold pressing process of multiple single-layer structures is complicated, and it is impossible to avoid the change of the original compaction density and porosity of each single layer during the cold pressing process again, and the joints between the layers are prone to delamination due to loose bonding, which affects the conduction of electrons and ions and deteriorates the cycle performance. In other technologies, lasers are used to punch holes in the active material layer, but laser drilling is inefficient, costly, and energy density is easily lost during the drilling process. In other technologies, a pore-forming agent solution is applied to the electrode surface, but this cannot avoid the dissolution of the electrode surface, and the depth of the holes formed by the pore-forming agent is limited, which has limited improvement on the near-current collector side. The above technologies solve the problem of ion transport from electrolyte to the surface of active material through different methods, but the ion transport from the surface of active material to the inside of active material layer remains unchanged, the obstacle of ion transport still exists, and the improvement effect is not good.
[0020] Some embodiments of the present application provide an electrode that can improve the conductivity of the active material layer of the electrode, thereby facilitating the improvement of the energy density of the electrochemical device using the electrode. In some embodiments, the electrode can be an electrode sheet; the electrode includes a current collector and an active material layer located on one side or both sides of the current collector; the active material layer is subjected to thermogravimetric analysis at a heating rate of 10°C / min in an inert atmosphere, and the results of the thermogravimetric analysis show that the mass change of the active material layer at 200°C to 350°C is 0% to 0.2%.
[0021] In some embodiments, if the active material layer contains a polymer compound with a low decomposition temperature (e.g., a polymer compound with a decomposition temperature lower than 350°C), such as a polymer thickener, when a thermogravimetric analysis is performed in the range of 200°C to 350°C, a weight loss peak will be generated due to thermal decomposition, and the mass change of the active material layer in the present application from 200°C to 350°C is 0% to 0.2%, which indicates that the active material layer in the embodiment of the present application contains almost no polymer compound with a low decomposition temperature, so that the influence of the polymer compound with a low decomposition temperature in the active material layer on the conductivity of the active material layer can be avoided, thereby improving the conductivity of the active material layer for ions and electrons, so that when the thickness of the active material layer is increased to increase the energy density of the electrochemical device, the active material layer has good conductivity, so the electrical performance of the electrochemical device will not be deteriorated due to the increase in the thickness of the active material layer. It can be seen from this that the electrode proposed in the embodiment of the present application is beneficial to improving the performance of the electrochemical device using the electrode and the energy density because the active material layer has good conductivity.
[0022] In some embodiments of the present application, the results of thermogravimetric analysis show that the number of weight loss peaks of the active material layer at 200°C to 350°C is 0, which indicates that there is almost no high molecular compound with a low decomposition temperature in the embodiments of the present application. In some embodiments of the present application, the results of thermogravimetric analysis show that the number of weight loss peaks of the active material layer at 350°C to 800°C is not less than 1, which indicates that there is a high molecular compound with a high decomposition temperature in the active material layer of the present application (decomposed into a high molecular compound with a temperature of 350°C to 800°C), because the high molecular compound needs to be used in the active material layer to make the substances in the active material layer bonded to each other and attached between the current collectors.
[0023] In some embodiments of the present application, the results of thermogravimetric analysis show that the mass change of the active material layer at 350°C to 800°C is 0.21% to 13%. This indicates that the content of the high molecular compound with a high decomposition temperature is not zero, which is conducive to ensuring the overall polymerization force of the active material layer and the bonding force with the current collector, and preventing the excessive influence of the polymer compound on the conductivity. Optionally, the results of thermogravimetric analysis show that the mass change of the active material layer at 350°C to 800°C is 0.77% to 3.4%, thereby balancing the requirements of conductivity and bonding force.
[0024] In some embodiments of the present application, the electrode is a negative electrode, for example, a negative electrode of an electrochemical device. In some embodiments, the electrode is a negative electrode, the active material layer is an active material layer of a negative electrode, and the current collector is a current collector of a negative electrode. The current collector can be copper foil, aluminum foil, steel foil, etc., without limitation. In some embodiments, the compaction density of the active material layer is ρ ≥ 0.6 g / cm 3 , a higher compaction density indicates that the mass of the active material layer carried by the electrode per unit volume is greater, and a greater mass of the active material layer can help increase the energy that can be stored per unit volume, thereby increasing the energy density. In some embodiments, the compaction density ρ of the active material layer satisfies: 1.85 g / cm 3 ≥ρ≥0.65g / cm 3 This is beneficial to improve the energy density. In some embodiments, by limiting the compaction density of the active material layer to no less than 0.65 g / cm 3 The energy density can be further guaranteed, and the compaction density of the negative electrode active material layer is limited to no more than 1.85 g / cm 3 It can prevent the particles in the active material layer from breaking due to excessive compaction density, thereby increasing the consumption of electrolyte and deteriorating the cycle performance. Optional, 1.83g / cm 3 ≥ρ≥1.0g / cm 3 .
[0025] In some embodiments, the thickness of the active material layer on one side of the current collector is h ≥ 10 μm. In some embodiments, a thicker active material layer is beneficial to increase the proportion of the active material layer, thereby increasing the energy density. In some embodiments of the present application, the thickness h of the active material layer on one side of the current collector satisfies: 1500 μm ≥ h ≥ 15 μm. By limiting the thickness of the active material layer to be not less than 15 μm, the thickness of the negative electrode active material layer can be guaranteed, thereby improving the energy density. By limiting the thickness of the negative electrode active material layer to be not more than 1500 μm, the problem of separation between the negative electrode active material layer and the current collector that may occur due to the negative electrode active material layer being too thick can be prevented. Optionally, 150 μm ≥ h ≥ 30 μm.
[0026] In some embodiments, the bonding force F between the active material layer and the current collector satisfies: 300 N / m ≥ F ≥ 0.5 N / m. Too small a bonding force between the active material layer and the current collector may cause desorption between the active material layer and the current collector, thereby deteriorating the conductivity. Too large a bonding force between the active material layer and the current collector may increase the demand for a binder and is not conducive to conductivity. Optionally, the bonding force F between the active material layer and the current collector satisfies: 150 N / m ≥ F ≥ 1 N / m, and optionally, 20 N / m ≥ F ≥ 1 N / m.
[0027] In some embodiments, the resistivity of the active material layer is 0.01 Ω*cm to 50 Ω*cm, which indicates that the negative electrode active material layer of the application has good conductivity and is beneficial to electrical performance. In some embodiments, the negative electrode active material layer includes a negative electrode material, and the negative electrode material includes at least one of lithium titanate, silicon oxide, graphite, silicon or hard carbon. The negative electrode material can be, for example, a combination of at least two of the above materials.
[0028] In some embodiments of the present application, the active material layer includes a conductive agent, and the conductive agent includes at least one of carbon nanotubes, carbon fibers, acetylene black, graphene, Ketjen black or conductive carbon black. The conductive agent can increase the conductivity of the active material layer. Among them, the carbon nanotubes can be single-walled carbon nanotubes or multi-walled carbon nanotubes, and the single-walled carbon nanotubes can increase long-range electron conduction while reducing the coating area of the binder on the active material, reducing the ion transmission barrier, and improving the kinetic performance. In some embodiments, the active material layer includes a conductive agent, and the mass percentage of the conductive agent in the active material layer is 0% to 2% based on the total mass of the active material layer. In some embodiments, the mass percentage of the conductive agent in the active material layer in the embodiment of the present application can be 0%, because in the embodiment of the present application, there is no polymer compound with a low decomposition temperature in the active material layer, and the polymer compound with a low decomposition temperature can be a binder and / or thickener from the electrode, which already has good conductivity, so the conductive agent can be added without adding the conductive agent, and the mass percentage of the conductive agent is limited to not more than 2%, thereby avoiding the capacity of the active material layer due to excessive conductive agent content.
[0029] In some embodiments of the present application, the active material layer includes a polymer compound, and the polymer compound includes at least one of polyethylene oxide, polypropylene oxide, polyvinylidene fluoride, polytetrafluoroethylene, polyacrylonitrile, polyimide, polysiloxane, polyacrylic acid, polypropylene derivatives, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polymethyl pyrrolidone, polyvinyl pyrrolidone, styrene acrylate or styrene-butadiene rubber. The polymer compound can be at least one of a binder or a thickener.
[0030] In some embodiments of the present application, the active material layer includes a polymer compound, and the mass percentage of the polymer compound in the active material layer is 0.22% to 14% based on the total mass of the active material layer. Too low a mass percentage of the polymer compound may result in insufficient adhesion between the active material layer and the current collector, and too high a mass percentage of the polymer compound may affect the conductivity of the active material layer. Optionally, the mass percentage of the polymer compound in the active material layer is 0.8% to 3.5%.
[0031] In some embodiments of the present application, a polymer compound (which may be a binder) is distributed in a point-like or surface-like manner on the surface of an active material (e.g., a negative electrode material) in an active material layer, and is concentrated on the surface of the active material or between particles of the active material. The active material is more exposed, and there is less hindrance to the transmission of electrons and ions, which is beneficial to ensuring conductivity.
[0032] For some examples, please refer to Figure 1The electrode includes a current collector 10 and an active material layer, the active material layer includes an active material 20, a conductive agent 30, and a binder 40, wherein the conductive agent may include a zero-dimensional conductive agent, a one-dimensional conductive agent, and a two-dimensional conductive agent, and the binder 40 may include a first binder and a second binder, wherein conductive agents of different dimensions can be fully filled in the gaps between the active materials, thereby improving the overall conductivity.
[0033] In some embodiments of the present application, a method for preparing an electrode is proposed, which can be used to manufacture any electrode of the present application, comprising: coating a slurry of an active material layer on at least one surface of a current collector, drying, and cold pressing to obtain an initial electrode; treating the initial electrode to obtain an electrode; wherein treating the initial electrode comprises: plasma treating the initial electrode in a vacuum environment, the plasma power is 0.5kW to 5kW, the gas source comprises at least one of nitrogen, argon or carbon tetrafluoride, the gas flow rate is 3000sccm to 5000sccm, the temperature is 20°C to 60°C, and the treatment time is 1min to 60min; or, heat treating the initial electrode in a vacuum or inert gas environment, the heat treatment temperature is 200°C to 400°C, and the heat treatment time is not less than 5min; or, laser bombarding the initial electrode in a vacuum or inert gas environment, the laser intensity is 25W to 30W, and the treatment time is 1s to 600s.
[0034] The method for preparing the electrode proposed in the embodiments of the present application can remove the polymer compound with a low decomposition temperature in the active material layer by treating the initial electrode, which is beneficial to improving the conductivity of the electrochemical device, and further to improving the energy density. In some embodiments of the present application, the active material layer of the electrode includes an active material, a conductive agent and a binder, and does not include a polymer compound with a low decomposition temperature (such as a polymer binder and / or thickener with a low decomposition temperature), thereby avoiding the obstruction of the polymer compound to the transmission of electrons and ions.
[0035] In some embodiments of the present application, the initial electrode is subjected to plasma treatment in a vacuum environment, the plasma power is 1 kW to 3 kW, and the treatment time is 15 min to 30 min. The treatment time can be reduced by increasing the plasma power. In other embodiments of the present application, the initial electrode is subjected to plasma treatment in a vacuum environment, the plasma power is 3 kW to 5 kW, and the treatment time is 1 min to 15 min.
[0036] In some embodiments of the present application, the initial electrode is heat treated in a vacuum or inert gas environment, the heat treatment temperature is 200°C to 250°C, and the heat treatment time is 180min to 300min. In other embodiments of the present application, the initial electrode is heat treated in a vacuum or inert gas environment, the heat treatment temperature is 250°C to 350°C, and the heat treatment time is 5min to 180min. The time for heat treatment of the initial electrode is related to the heat treatment temperature. Increasing the heat treatment temperature can reduce the heat treatment time, and extending the heat treatment time can reduce the heat treatment temperature.
[0037] In some embodiments of the present application, the electrochemical device includes an electrode; the electrode is any electrode of the present application; or, the electrode is an electrode prepared by the preparation method proposed in the present application. In some embodiments, the electrochemical device includes a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode. In some embodiments, the negative electrode can be any of the above electrodes. In some embodiments, the current collector of the positive electrode can be Al foil, and of course, other current collectors commonly used in the art can also be used.
[0038] In some embodiments, the separator includes at least one of polyethylene, polypropylene, polyvinylidene fluoride, polyethylene terephthalate, polyimide or aramid. For example, polyethylene includes at least one selected from high-density polyethylene, low-density polyethylene or ultra-high molecular weight polyethylene. In particular, polyethylene and polypropylene have a good effect on preventing short circuits and can improve the stability of the battery through the shutdown effect. In some embodiments, the thickness of the separator is in the range of about 5 μm to 50 μm.
[0039] In some embodiments, the surface of the isolation membrane may further include a porous layer, the porous layer is disposed on at least one surface of the isolation membrane, the porous layer includes inorganic particles and a binder, the inorganic particles are selected from at least one of aluminum oxide (Al2O3), silicon oxide (SiO2), magnesium oxide (MgO), titanium oxide (TiO2), hafnium dioxide (HfO2), tin oxide (SnO2), cerium dioxide (CeO2), nickel oxide (NiO), zinc oxide (ZnO), calcium oxide (CaO), zirconium oxide (ZrO2), yttrium oxide (Y2O3), silicon carbide (SiC), boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. In some embodiments, the pores of the isolation membrane have a diameter in the range of about 0.01 μm to 1 μm. The binder of the porous layer is selected from at least one of polyvinylidene fluoride, copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene or polyhexafluoropropylene. The porous layer on the surface of the separator can improve the heat resistance, oxidation resistance and electrolyte wetting performance of the separator, and enhance the adhesion between the separator and the pole piece.
[0040] In some embodiments of the present application, the electrochemical device may be wound or stacked. In some embodiments, the positive electrode and / or negative electrode of the electrochemical device may be a multilayer structure formed by winding or stacking, or a single-layer structure in which a single-layer positive electrode, a separator, and a single-layer negative electrode are stacked.
[0041] In some embodiments, the electrochemical device includes a lithium ion battery, but the present application is not limited thereto. In some embodiments, the electrochemical device may further include an electrolyte. The electrolyte may be one or more of a gel electrolyte, a solid electrolyte, and an electrolyte, the electrolyte including a lithium salt and a non-aqueous solvent. The lithium salt is selected from one or more of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, LiSiF6, LiBOB or lithium difluoroborate. For example, the lithium salt is selected from LiPF6 because it has high ionic conductivity and can improve cycle characteristics.
[0042] The non-aqueous solvent may be a carbonate compound, a carboxylate compound, an ether compound, other organic solvents or a combination thereof. The carbonate compound may be a linear carbonate compound, a cyclic carbonate compound, a fluorinated carbonate compound or a combination thereof.
[0043] Examples of chain carbonate compounds are diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC) and combinations thereof. Examples of cyclic carbonate compounds are ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinyl ethylene carbonate (VEC) or combinations thereof. Examples of fluorocarbonate compounds are fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, trifluoromethylethylene carbonate or combinations thereof.
[0044] Examples of the carboxylic acid ester compound are methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanolide, valerolactone, mevalonolactone, caprolactone, methyl formate, or a combination thereof.
[0045] Examples of the ether compound are dibutyl ether, tetraglyme, diglyme, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, or a combination thereof.
[0046] Examples of other organic solvents are dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate, and phosphoric acid esters or combinations thereof.
[0047] In some embodiments of the present application, taking a lithium-ion battery as an example, a positive electrode, a separator, and a negative electrode are wound or stacked in sequence to form an electrode component, and then encapsulated in, for example, an aluminum-plastic film, injected with an electrolyte, formed, and encapsulated to form a lithium-ion battery. Then, the prepared lithium-ion battery is subjected to a performance test.
[0048] Those skilled in the art will appreciate that the above-described method for preparing an electrochemical device (eg, a lithium-ion battery) is only an example, and other methods commonly used in the art may be used without departing from the disclosure of the present application.
[0049] The present application proposes an electronic device, including an electrochemical device; the electrochemical device is an electrochemical device of any one of the present application. The electronic device of the embodiment of the present application is not particularly limited, and it can be any electronic device known in the prior art. In some embodiments, the electronic device may include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power bicycle, a bicycle, a drone, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera or a large household battery, etc.
[0050] Some specific embodiments and comparative examples are listed below to better illustrate the present application, wherein a lithium-ion battery is used as an example.
[0051] Example 1
[0052] Preparation of positive electrode sheet: The positive electrode material lithium cobalt oxide, polyvinylidene fluoride (PVDF), and conductive agent carbon nanotube (CNT) are mixed in a mass ratio of 97.5:1:4.5, and N-methylpyrrolidone (NMP) is used as a solvent to prepare a slurry, which is then stirred evenly to form a slurry of the positive electrode active material layer. The slurry is evenly coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is obtained after drying.
[0053] Preparation of negative electrode sheets: negative electrode material graphite, binder styrene acrylate, binder styrene butadiene rubber, conductive agent carbon nanotubes, and thickener sodium carboxymethyl cellulose are mixed in a mass ratio of 98.56:0.62:0.62:0.2:1, and deionized water is used as a solvent to form a negative electrode active material layer slurry. Copper foil is used as a negative electrode collector, and the slurry of the negative electrode active material layer is coated on the negative electrode collector, and dried at 90°C. The dried electrode sheet is heat-treated at a heat treatment temperature of 360°C and a heat treatment time of 10 minutes to obtain a negative electrode sheet after heat treatment.
[0054] Preparation of isolation film: The isolation film is 8 μm thick polyethylene (PE).
[0055] Preparation of electrolyte: In an environment with a water content of less than 10 ppm, lithium hexafluorophosphate and a non-aqueous organic solvent (ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC): propyl propionate (PP): vinylene carbonate (VC) = 20:30:20:28:2, weight ratio) are prepared in a weight ratio of 8:92 to form an electrolyte.
[0056] Preparation of lithium-ion battery: stack the positive electrode sheet, separator, and negative electrode sheet in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and wind them to obtain the electrode assembly. Place the electrode assembly in the outer packaging aluminum plastic film, remove moisture at 80°C, inject the above electrolyte and package, and obtain the lithium-ion battery through the process of formation, degassing, trimming, etc.
[0057] The relevant parameters of Example 1 are as follows: the negative electrode active material layer includes graphite, styrene acrylate, styrene butadiene rubber and CNT, and the mass percentages of graphite, styrene acrylate, styrene butadiene rubber and CNT are 98.56%, 0.62%, 0.62% and 0.2% respectively. The binder of the negative electrode active material is styrene acrylate and styrene butadiene rubber in a mass ratio of 1:1. The mass content of the polymer compound in the negative electrode active material layer is 1.24%, and the compaction density of the negative electrode active material layer is 1.75g / cm 3The thickness of the active material layer on one side of the negative electrode current collector is 75 μm, the bonding force between the active material layer of the negative electrode and the current collector is 11 N / m, the resistivity of the active material layer of the negative electrode is 0.1 Ω*cm, the negative electrode material is graphite, the conductive agent is carbon nanotubes (CNT), the mass percentage of the conductive agent in the active material layer of the negative electrode is 0.2%, the number of weight loss peaks of the active material layer of the negative electrode from 200°C to 350°C is 0, the mass change from 200°C to 350°C is 0.10%, the number of weight loss peaks from 350°C to 800°C is 2, and the mass change from 350°C to 800°C is 1.25%. The positive electrode active material layer includes lithium cobalt oxide, PVDF and CNT, wherein the mass percentages of lithium cobalt oxide, PVDF and CNT are 97.5%, 1% and 1.5%, the thickness of the single side of the positive electrode is 63 microns, and the compaction density is 4.12 g / cm 3 .
[0058] Other embodiments are based on the steps of Example 1 with parameter changes. The specific changed parameters are shown in the table below. In each embodiment, the same amount of sodium carboxymethyl cellulose is added to the slurry of the negative electrode active material layer and then removed by heat treatment.
[0059] Comparative Example 1
[0060] Preparation of negative electrode sheet: negative electrode material graphite, binder styrene acrylate, and thickener sodium carboxymethyl cellulose are mixed in a mass ratio of 97:2:1.0, deionized water is used as solvent to form a negative electrode active material layer slurry, copper foil is used as the negative electrode collector, the slurry of the negative electrode active material layer is coated on the negative electrode collector, and dried at 90°C to obtain a negative electrode sheet.
[0061] The remaining preparation steps of Comparative Example 1 are the same as those of Example 1. The differences in parameters between Comparative Example 1 and Example 1 are shown in the table below.
[0062] Comparative Example 2
[0063] Preparation of negative electrode sheet: negative electrode material graphite, conductive agent carbon nanotubes, binder styrene-butadiene rubber, and thickener sodium carboxymethyl cellulose are mixed in a mass ratio of 97.2:0.3:1.5:1.0, deionized water is used as solvent to form a negative electrode active material layer slurry, copper foil is used as the negative electrode current collector, the slurry of the negative electrode active material layer is coated on the negative electrode current collector, and dried at 90°C to obtain a negative electrode sheet.
[0064] The remaining preparation steps of Comparative Example 2 are the same as those of Example 1. The differences in parameters between Comparative Example 2 and Example 1 are shown in the table below.
[0065] Comparative Example 3
[0066] Preparation of negative electrode sheet: negative electrode material graphite, conductive agent carbon nanotubes, binder polyacrylate, and thickener sodium carboxymethyl cellulose are mixed in a mass ratio of 94.9:0.1:4:1.0, deionized water is used as solvent to form a negative electrode active material layer slurry, copper foil is used as the negative electrode collector, the slurry of the negative electrode active material layer is coated on the negative electrode collector, and dried at 90°C to obtain a negative electrode sheet.
[0067] The remaining preparation steps of Comparative Example 3 are the same as those of Example 1. The differences in parameters between Comparative Example 3 and Example 1 are shown in the table below.
[0068] The test methods of the present application are described below.
[0069] 1. Thermogravimetric test
[0070] The battery was discharged to 3.0V, and the battery was disassembled to obtain the negative electrode plate. The plate was soaked in DMC (dimethyl carbonate) for 12 to 24 hours, and then the DMC was replaced and soaked for another 12 to 24 hours, and dried at 80°C to 100°C. The active material layer powder at the corresponding position was scraped from the surface of the plate for testing. The active material layer of the negative electrode of the prepared lithium-ion battery was determined by thermogravimetric analysis to perform thermogravimetric analysis. The mass change and the number of weight loss peaks during the thermogravimetric analysis were tested. The test range was 200°C to 350°C and 350°C to 800°C, the heating rate was 10°C / min, and the test atmosphere was an inert atmosphere.
[0071] 2. Resistivity test
[0072] The resistivity of the active material layer is tested using a resistance tester. The upper and lower plane controllable pressure probes are used to directly measure the pole piece. AC current is applied to the positive pole piece or negative pole piece to be tested. At the same time, a certain pressure (0.35T) is applied to the active material layer to obtain the overall resistance in the thickness direction of the pole piece. At the same time, the area (A) and thickness (l) of the pole piece to be tested are collected. The resistivity of the pole piece to be tested is derived according to the resistivity calculation formula (ρ=R*A / l). 3. AC resistance test
[0073] A small 1Khz AC current is applied to the positive and negative electrodes of the battery, and the AC resistance of the battery is obtained by measuring the voltage response.
[0074] 4. 25℃ DC resistance DCR test
[0075] At 25°C, charge the lithium-ion battery to 4.45V at 0.5C, then charge to 0.05C at constant voltage; let stand for 30 minutes; discharge at 0.1C for 3 hours until the battery state of charge is 70% SOC (record the corresponding discharge end voltage value U1), and discharge at 1C for 1 second (record the corresponding discharge end voltage value U2). Among them, "1C" is the current value that completely discharges the battery capacity within 1 hour. The DCR of the battery at 70% SOC is calculated according to the following formula: DCR = (U1-U2) / (1C-0.1C).
[0076] 5. Rate performance test
[0077] In an environment of 25℃, the battery was discharged to 3V at a constant current, and the first charge and discharge were performed. Constant current charging was performed at a charging current of 0.7C until the upper limit voltage was 4.48V, and then constant voltage charging was performed to 0.05C, and then constant current discharge was performed at a discharge current of 0.2C until the final voltage was 3V. At this time, the discharge capacity of 0.2C was recorded, and then the battery was repeatedly charged at a charging current of 0.7C until the upper limit voltage was 4.48V, and then constant voltage charging was performed to 0.05C, and then the discharge rate was set to 3C constant current discharge until the final voltage was 3V, and the discharge capacity of 3C was recorded at this time.
[0078] 3C discharge capacity retention rate = (3C discharge capacity / 0.2C discharge capacity) × 100%
[0079] 6. Cycle performance test
[0080] Charge to 4.2V at 0.5C rate, then change to 4.21V constant voltage charging until the current drops to 0.025C. After standing for 5 minutes, discharge to 3.0V at 0.5C rate, completing one cycle. Record the discharge capacity as the capacity of the lithium-ion battery. Repeat 1000 cycles, record the discharge capacity as the remaining capacity of the lithium-ion battery. 1000 cycle capacity retention rate = remaining capacity / initial capacity × 100%.
[0081] Table 1
[0082]
[0083]
[0084]
[0085] Note: The active material layer in this application table refers to the active material layer of the negative electrode, the bonding force refers to the bonding force between the active material layer of the negative electrode and the current collector, the contents in the table are all mass percentages, and the parameters not shown in Table 1 Examples and Comparative Examples are the same as those in Example 1.
[0086] Please refer to Table 1, which shows the preparation parameters and performance test results of Examples 1 to 9 and Comparative Examples 1 to 3, wherein the preparation parameters not shown in Table 1 are the same. It can be seen from Table 1 that the mass change of the negative electrode active material layer at 200°C to 350°C in Examples 1 to 9 is 0% to 0.2%, the number of weight loss peaks of the negative electrode active material layer at 200°C to 350°C is 0, and the number of weight loss peaks at 350°C to 800°C is not 0. The mass change of the negative electrode active material layer at 200°C to 350°C in Comparative Examples 1 to 9 is greater than 0.2%, the number of weight loss peaks of the negative electrode active layer at 200°C to 350°C is not 0, and the number of weight loss peaks at 350°C to 800°C is also not 0. It can be seen from Table 1 that the AC resistance and DC resistance of the lithium ion batteries in Examples 1 to 9 are significantly smaller than those in Comparative Examples 1 to 3, and the capacity retention rate after 3C rate discharge in Examples 1 to 9 is significantly higher than that in Comparative Examples 1 to 3. It can be seen from the above data that when the active material layer is subjected to thermogravimetric analysis at 200°C to 350°C, when the mass change of the negative electrode active material layer at 200°C to 350°C is 0% to 0.2%, the conductivity of the active material layer can be improved, thereby reducing the resistance of the electrochemical device, which is beneficial to improving the rate performance. This is because the active material layer of the negative electrode in Examples 1 to 9 is heat-treated to remove the high-molecular compound with a low decomposition temperature, thereby improving the conductivity. Therefore, the lithium-ion batteries all have good conductivity and rate performance.
[0087] As shown in Comparative Examples 1 to 3, as the mass change in the thermogravimetric analysis process from 200°C to 350°C increases, the AC resistance and DC resistance of the lithium ion battery increase. This may be because the mass change in the thermogravimetric process from 200°C to 350°C reflects the content of high molecular weight compounds with low decomposition temperatures, and the increase in the content of high molecular weight compounds with low decomposition temperatures is not conducive to the conductivity of the lithium ion battery.
[0088] As shown in Examples 1 to 4, the number of weight loss peaks of the negative electrode active material layer at 350°C to 800°C is related to the type of binder, and one type of binder corresponds to one weight loss peak. When the binder is styrene acrylate, the AC resistance and DC resistance are the smallest, and the 3C discharge capacity retention rate is the highest.
[0089] As shown in Examples 5 to 9, as the mass change of the negative electrode active material layer during the thermogravimetric analysis process from 350°C to 800°C increases, the conductivity of the lithium ion battery begins to decrease, and the 3C discharge capacity retention rate decreases slightly. This may be because the mass change during the thermogravimetric analysis process from 350°C to 800°C reflects the content of the polymer binder with a high decomposition temperature. An increase in the binder content is not conducive to the conductivity and discharge performance of the lithium ion battery. The higher the mass percentage of the binder, the greater the bonding force, but the higher the AC resistance and DC resistance, and the 3C discharge capacity retention rate is affected. However, too small a bonding force may cause separation between the negative electrode active material layer and the current collector.
[0090] Table 2
[0091]
[0092]
[0093] The parameters of Examples 7, 10 to 17 differ from those of Example 1 only in the data shown in Table 2, and the other parameters not shown are the same as those of Example 1.
[0094] As shown in Examples 10, 11, 7, 12 to 13, as the compaction density of the active material layer of the negative electrode increases, the bonding force increases, the resistivity decreases, the AC resistance gradually decreases, the DC resistance first increases and then decreases, the 3C discharge capacity retention first decreases and then increases, and the 1000-cycle capacity retention first decreases and then increases. This may be because the increase in the compaction density reduces the distance that ions and electrons are transmitted between particles, thereby increasing conductivity and reducing resistance. However, when the compaction density is too large, it may result in insufficient electrolyte infiltration, which may be detrimental to the performance of the lithium-ion battery.
[0095] As shown in Examples 14, 15, 7, 16 to 17, as the thickness of the active material layer on one side of the negative electrode current collector increases, the bonding force of the lithium ion battery decreases, the AC resistance and DC resistance increase, and the 3C discharge capacity retention rate and the 1000 cycle capacity retention rate decrease. This may be because the increase in the thickness of the negative electrode active material layer leads to an increase in the path for ion and electron transmission, which is not conducive to conductivity and deteriorates the kinetic performance. However, if the thickness of the negative electrode active material layer is too small, the capacity that the negative electrode can store will be reduced, which is not conducive to energy density. Therefore, a balance between the performance and capacity density of the lithium ion battery is considered.
[0096] Table 3
[0097]
[0098]
[0099]
[0100] The parameters of Examples 18 to 28 differ from those of Example 1 only in the data shown in Table 3, and the remaining parameters not shown are the same as those of Example 1.
[0101] As shown in Examples 18 to 22, when the negative electrode material is silicon dioxide, lithium titanate, graphite, silicon or hard carbon, the lithium-ion batteries all have relatively balanced performance. Among them, when the negative electrode material is hard carbon, the performance is the best, but the compaction density is lower. When the negative electrode material is graphite, the overall performance is the best.
[0102] As shown in Examples 23 to 27, when the conductive agent is conductive carbon black, acetylene black, Ketjen black, carbon nanotubes, graphene, or carbon fiber, the lithium-ion batteries have smaller resistivity, AC resistance, and DC resistance, and a higher 3C discharge capacity retention rate. This shows that when the conductive agent includes the above materials, the performance requirements of the lithium-ion battery can be met.
[0103] As shown in Examples 7, 20 and 28, the resistivity of the active material layer of the negative electrode was adjusted by adjusting the content of carbon nanotubes in the active material layer. As the conductive agent in the active material layer of the negative electrode increased, the resistivity decreased, the AC resistance and DC resistance of the lithium-ion battery both decreased, and the 3C discharge capacity retention rate increased. This is because the resistivity of the active material layer improved the conductivity of the lithium-ion battery and improved the performance of the lithium-ion battery, but too much conductive agent may lead to a decrease in energy density.
[0104] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of disclosure involved in the present application is not limited to the technical solution formed by a specific combination of the above technical features, but should also cover other technical solutions formed by any combination of the above technical features or their equivalent features. For example, the above features are replaced with the technical features with similar functions disclosed in the present application.
Claims
1. An electrode, characterized in that: include: A current collector and an active material layer disposed on at least one surface of the current collector; The active material layer is subjected to a thermogravimetric analysis at a heating rate of 10° C. / min under an inert atmosphere, wherein the result of the thermogravimetric analysis shows that the mass change of the active material layer at 200° C. to 350° C. is 0% to 0.2%, and the result of the thermogravimetric analysis shows that the number of weight loss peaks of the active material layer at 350° C. to 800° C. is not less than 1; The result of the thermogravimetric analysis shows that the weight loss peak number of the active material layer at 200° C. to 350° C. is 0; The results of the thermogravimetric analysis showed that the mass change of the active material layer at 350° C. to 800° C. was 0.21% to 13%.
2. The electrode according to claim 1, characterized in that The results of the thermogravimetric analysis showed that the mass change of the active material layer at 350° C. to 800° C. was 0.77% to 3.4%.
3. The electrode according to claim 1, characterized in that The electrode is a negative electrode.
4. The electrode according to claim 3, characterized in that The electrode satisfies at least one of the following conditions: (a) The compaction density of the active material layer is ρ≥0.6 g / cm 3 ; (b) the thickness of the active material layer on one side of the current collector is h≥10 μm; (c) the bonding force F between the active material layer and the current collector satisfies: 300 N / m ≥ F ≥ 0.5 N / m; (d) the resistivity of the active material layer is 0.01 Ω*cm to 50 Ω*cm; (e) The active material layer includes a negative electrode material, and the negative electrode material includes at least one of lithium titanate, silicon oxide, graphite, silicon or hard carbon.
5. The electrode according to claim 3, characterized in that The electrode satisfies at least one of the following conditions: (f) The compaction density ρ of the active material layer satisfies: 1.85 g / cm 3 ≥ρ≥0.65g / cm 3 ; (g) the thickness h of the active material layer on one side of the current collector satisfies: 1500 μm ≥ h ≥ 15 μm; (h) The bonding force F between the active material layer and the current collector satisfies: 150 N / m ≥ F ≥ 1 N / m.
6. The electrode according to claim 3, characterized in that The electrode satisfies at least one of the following conditions: (i) The compaction density ρ of the active material layer satisfies: 1.83 g / cm 3 ≥ρ≥1.0g / cm 3 ; (j) the thickness h of the active material layer on one side of the current collector satisfies: 150 μm ≥ h ≥ 30 μm; (k) The bonding force F between the active material layer and the current collector satisfies: 20 N / m ≥ F ≥ 1 N / m.
7. The electrode according to claim 1, characterized in that The active material layer includes a conductive agent, and the conductive agent includes at least one of carbon nanotubes, carbon fibers, acetylene black, graphene, Ketjen black, or conductive carbon black.
8. The electrode according to claim 1, characterized in that The active material layer includes a conductive agent, and based on the total mass of the active material layer, the conductive agent has a mass percentage in the active material layer of 0% to 2%.
9. The electrode according to claim 1, characterized in that The active material layer includes a polymer compound, and the polymer compound includes at least one of polyethylene oxide, polypropylene oxide, polyvinylidene fluoride, polytetrafluoroethylene, polyacrylonitrile, polyimide, polysiloxane, polyacrylic acid, polypropylene derivatives, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polymethyl pyrrolidone, polyvinyl pyrrolidone, styrene acrylate or styrene-butadiene rubber.
10. The electrode according to claim 1, characterized in that The active material layer includes a polymer compound, and based on the total mass of the active material layer, the mass percentage of the polymer compound in the active material layer is 0.22% to 14%.
11. The electrode according to claim 1, characterized in that The active material layer includes a polymer compound, and based on the total mass of the active material layer, the mass percentage of the polymer compound in the active material layer is 0.8% to 3.5%.
12. A method for preparing an electrode according to any one of claims 1 to 11, characterized in that: include: The slurry of the active material layer is applied to at least one surface of the current collector, dried, and cold pressed to obtain an initial electrode, wherein the active material layer of the initial electrode includes a high molecular compound with a decomposition temperature of 350° C. to 800° C.; Treating the initial electrode and ensuring that the active material layer contains the high molecular compound with a high decomposition temperature after the treatment, thereby obtaining the electrode; Wherein, processing the initial electrode comprises: The initial electrode is subjected to plasma treatment in a vacuum environment, wherein the plasma power is 0.5 kW to 5 kW, the gas source comprises at least one of nitrogen, argon or carbon tetrafluoride, the gas flow rate is 3000 sccm to 5000 ccm, the temperature is 20° C. to 60° C., and the treatment time is 1 min to 60 min; or, Heat treating the initial electrode in a vacuum or inert gas environment at a temperature of 200° C. to 400° C. for a time of not less than 5 minutes; or, The initial electrode is subjected to laser bombardment in a vacuum or inert gas environment, the laser intensity is 25W to 30W, and the processing time is 1s to 600s.
13. The preparation method according to claim 12, characterized in that: Performing plasma treatment on the initial electrode in a vacuum environment, with a plasma power of 1 kW to 3 kW and a treatment time of 15 min to 30 min; or, The initial electrode is subjected to plasma treatment in a vacuum environment, the plasma power is 3 kW to 5 kW, and the treatment time is 1 min to 15 min.
14. The preparation method according to claim 12, characterized in that: The initial electrode is heat treated in a vacuum or inert gas environment at a temperature of 200° C. to 250° C. for a time of 180 min to 300 min; or, The initial electrode is heat treated in a vacuum or inert gas environment, the heat treatment temperature is 250° C. to 350° C., and the heat treatment time is 5 min to 180 min.
15. An electrochemical device, characterized in that: including electrodes; The electrode is an electrode as claimed in any one of claims 1 to 11, or, The electrode is an electrode prepared by the preparation method according to any one of claims 12 to 14.
16. An electronic device, characterized in that: Comprising the electrochemical device as claimed in claim 15.
Citation Information
Patent Citations
Non-aqueous electrolyte secondary battery
CN105103340A
Electrode and manufacturing method thereof, electrochemical device and electronic device
CN115380398A